Clinical Outcome After Anterior Lumbar Interbody Fusion With a New Osteoinductive Bone Substitute Material: A Randomized Clinical Pilot Study. Issue 7 (August 2019) - Rickert, Marcus; Fleege, Christoph; Papachristos, Ioannis; Makowski, Marcus R.; Rauschmann, Michael; Arabmotlagh, Mohammad
Abstract : Study Design: Pilot, single-center, single-blinded, parallel-group, randomized clinical study. Objective: The aim of this study was to pilot a randomized clinical study to evaluate whether instrumented anterior lumbar interbody fusion (ALIF) with a new nanocrystalline hydroxyapatite embedded in a silica gel matrix (NH-SiO2 ) leads to superior radiologic and clinical outcomes at 12-month follow-up compared with instrumented ALIF with homologous bone. Summary of Background Data: ALIF completed with interbody cages is an established technique for performing arthrodesis of the lumbar spine. There is ongoing discussion about which cage-filling material is most appropriate. This is the first study to assess the efficacy of NH-SiO2 in ALIF surgery. Materials and Methods: This randomized, clinical, pilot trial included 2 groups of 20 patients with monosegmental or multisegmental degenerative disease of the lumbar spine who were suitable to undergo monosegmental or bisegmental ALIF fusion at the level L4/L5 and L5/S1 with a carbon fiber reinforced polymer ALIF cage filled with either NH-SiO2 or homogenous bone. Primary outcome was postoperative disability as measured by the Oswestry Disability Index (ODI). Secondary outcomes were postoperative radiographic outcomes, pain, and quality of life. Patients were followed 12 months postoperatively. Results: Mean (±SD) 12-month ODI was 24±17 in the NH-SiO2 group and 27±19 in the homologous bone group ( P =0.582). Postoperative radiography, functional outcomes, and quality-of-life indices did not differ significantly between groups at any of the regularly scheduled follow-up visits. Conclusions: This clinical study showed similar functional, radiologic, and clinical outcomes 12 months postoperatively for instrumented ALIF procedures with the use of NH-SiO2 or homologous bone as cage filling. In the absence of any relevant differences in outcome, we postulate that the pivotal clinical study should be designed as an equivalence trial.